2252. Predictors of Cardiovascular Outcomes in Older HIV-Infected Patients: CORE50 Cohort 10-Year Follow-up. (26th November 2018) - Sansom, Sarah; Burke, Kerianne; Adeyemi, Oluwatoyin
Abstract: Background: Cardiovascular (CV) disease is increasingly recognized in HIV+ patients. Currently there are limited data on older HIV+ patients in regards to CV outcomes. The CORE50 study was a cross-sectional study of 121 HIV+ patients ≥ 50 years (83% African American) recruited 2005–2006 at the CORE Center. The goal of this study was to identify predictors of CV outcomes and the impact of the Framingham cardiac risk at baseline on CV outcomes and mortality >10 years later. Methods: Retrospective chart review was conducted in 2018 to evaluate HAART therapy, CD4, viral suppression, HCV coinfection or treatment history, comorbid conditions, BMI, renal function and current medications. Patients were evaluated for CV events (defined as myocardial infarction, cerebrovascular events, transient ischemic attacks and peripheral artery disease). Results: At follow-up, 60 (49%) patients with a mean age of 65 years remained in care at CORE. Mean CD4 count was 529 cells/mm 3 and 82% had undetectable HIVRNA. 22 patients had died (18%), 10(8%) had transferred care and 29(24%) lost to follow-up. The mean age at death was 61 years. The causes of death were CV (18.2%), cancer (36.4%), infection (18.5%) and other (27.2%; organ failure/overdose/unknown). On Univariate analysis, Framingham cardiac risk (FCR) of >10% at baseline (2005/2006) was associated with increased CV events ( P = 0.05). FCR >20% was associated with increased death ( P = 0.01). Smoking at baseline and follow-up were associated with increased CV events ( P = 0.05 and P = 0.035, respectively). Evaluation of medication regimen showed history of protease inhibitor use or current use of integrase inhibitor was associated with increased CV events ( P = 0.01 and P = 0.011, respectively). History of depression was associated with increased CV events ( P = 0.035). Aspirin use at initial assessment was associated with decreased death ( P < 0.000). Conclusion: This retrospective study shows that FCR, history of depression and smoking are associated with adverse outcomes in HIV patients. It suggests that the FCR is useful for risk stratification of cardiovascular disease in HIV patients. It is extremely important to identify and manage cardiac risk factors in older HIV patients to reduce cardiovascular morbidity and mortality. Disclosures: All authors: No reported disclosures.